Julie Coleman and Christian J. Kay (Eds.). Lexicology, Semantics and Lexicography: Selected Papers from the Fourth G.L. Brook Symposium, Manchester, August 1998. - Carstens, Adelia; van Huyssteen, Gerhard B. (Lexikos, 2002)
NVolume 194 of the series Current Issues in Linguistic Theory, entitled Lexicology,Semantics and Lexicography, comprises a selection of eleven academic contributionsthat were originally presented at the Tenth International Conference ofEnglish Historical Linguistics. The disciplinary focus of this volume of texts isthe diachronics of English vocabulary, and the representation thereof in dictionaries.From a theoretical point of view prototype theory assumes a centralposition, and the methodological approach is mainly corpus-analytical.